ESTIMATION OF HERITABILITY AND BREEDING VALUE OF PIGLET BIRTH WEIGHT - Bayu Dewantoro Putro Soewandi; V. M. Ani Nurgiartiningsih; Kuswati Kuswati (Widyariset, 2017)
Piglet birth weight has an economic value and commonly correlated with weaning weigh. Therefore, birth weight traits of piglet needs to be selected for genetic improvement. The purpose of a study was to estimate the genetic improvement of piglet birth weight based on heritability and breeding value. Around 154 heads of offsprings generated from 6 sires and 14 sows were used in this study. The data of piglet birth weight was analyzed for heritability (nested classification), breeding value, selection response, and genetic improvement estimation. The result showed that the heritability (h2) of offsprings was 0.24±0,15. Based on breeding value, sires which had high piglet birth weight can be used for male ranking. Selection of response value was 0.06 kg. According to the selection of response value, improvement of birth weight in piglet based on the sire used can be estimated.